Comparison of partially attended night time respiratory recordings and full polysomnography in patients with suspected sleep apnoea/hypopnoea syndrome. Issue 10 (October 1996) - Lloberes, P.; Montserrat, J. M.; Ascaso, A.; Parra, O.; Granados, A.; Alonso, P.; Vilaseca, I.; Rodriguez-Roisin, R.
Abstract : BACKGROUND: Laboratory full polysomnography (PSG) is considered to be the gold standard for the diagnosis of the sleep apnoea/hypopnoea syndrome (SAHS), but it is expensive and time consuming. A study was undertaken to evaluate the diagnostic usefulness of a partially attended night time respiratory recording (NTRR) and a clinical questionnaire in patients with suspected SAHS in comparison with full PSG. METHODS: Seventy six patients (54 men) of mean (SD) age 51 (11.5) years with a body mass index of 31 (5.7) kg/m2 were studied at random on two different nights with full PSG at the sleep laboratory and with NTRR on a respiratory ward. NTRR records oximetry, airflow, chest and abdominal motion. All signals were continuously displayed on a computer screen throughout the night and respiratory events were scored automatically the following morning. All patients completed a clinical questionnaire. RESULTS: Mean values of the apnoea/hypopnoea index (AHI) using NTRR were lower than those obtained with full PSG (22.7 (2.4) versus 32.2 (3) events/hour) which was mainly due to underrecognition of hypopnoeas. Sensitivity and specificity of NTRR for the diagnosis of SAHS were 82% and 90%, respectively, taking as reference AHI > 10 on full PSG (AHI-PSG > 10). The mean (+/-2SD) difference in AHI between the two methods was 9.6 (range -5.4-24.6) (95% confidence interval 6.2 to 13). Symptoms of witnessed apnoeas, impotence, the overall clinical impression of a trained physician, and a neck size over 40 cm were significantly more prevalent in patients with AHI-PSG of > 10, but impotence was the only clinical feature significantly more prevalent in patients with false negative compared with true negative NTRR results that helped to distinguish patients with NTRR < 10 but AHI-PSG > 10. CONCLUSIONS: NTRR is a helpful and easy complementary diagnostic tool in clinical practice because it detects patients with moderate to severe SAHS reasonably well and therefore can be useful for confirming a diagnosis of SAHS and also for treatment decisions. It is suggested that patients with suspicion of SAHS should be initially studied by NTRR. When NTRR is negative, a full PSG should be performed if witnessed apnoeas, impotence, systemic hypertension, ischaemic heart disease, and a trained physician's clinical impression of SAHS are present.